Friendship for development: a new model of development practice?. Issue 7 (3rd October 2022) - Wigglesworth, Ann
ABSTRACT: Friendship forms the basis of 35 community partnerships between Australia and Timor-Leste. Friendship facilitates the ownership of project activities by Timorese partners bringing into the development relationship a mutual respect and a shared journey of a kind that is not typical in time-bound aid projects. This paper reviews different models of donor-recipient relationships. A case study is used to show how Friendship offers a development strategy aligned with solidarity through a long term commitment built on trust and mutual responsibility. The model should be considered alongside the many existing theories and approaches to effective community development.